Republic of Moldova : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criterion and Augmentation of Access. (IMF Staff Country Reports; Country Report ;, 2007)
The First Review Under the Three-Year Arrangement under the Poverty Reduction and Growth Facility of the Republic of Moldova analyzes macroeconomic and structural policy measures to support the adjustment and promote growth. Moldova is facing serious external shocks that will have long-lasting effects. All quantitative performance criteria and indicative targets were met with the exception of the international reserves target, which was missed because of the shocks. Financial sector development is to be promoted by encouraging foreign competition in the banking system.